Digitalization of criminal proceedings as a means to protect the economic interests of business - Kapustian, Iryna Volodymyrivna; Kapustian, I. V.; Kuznetsova, Liudmyla Valentynivna; Kuznetsova, L. V.; Капустян, Ірина Володимірівна; Капустян, І. В.; Кузнєцова, Людміла Валентинівна; Кузнєцова, Л. В. (Одеса : Фенікс, 2026)
The contemporary challenges arising under martial law in Ukraine create fundamentally new conditions for the functioning of criminal proceedings, in which traditional mechanisms for ensuring procedural safeguards are often insufficient or objectively limited. The destruction of infrastructure, business relocation, and limited access to courts and physical information carriers necessitate the transformation of criminal proceedings on the basis of digitalization. In this context, the digitalization of criminal proceedings acquires both practical and systemic significance, ensuring the effective protection of business economic interests even under crisis conditions.
Kapustian, I. V., Kuznetsova, L. V. Digitalization of criminal proceedings as a means to protect the economic interests of business. Соціально-політична та правова система України в цифрову епоху: сучасні виклики : матеріали Міжнар. наук.-практ. конф. (м. Одеса, 22 квіт. 2026 р.) : у 2-х т. / заг. ред. С. Ківалова ; НУ «Одес. юрид. академія». Одеса : Фенікс, 2026. Т. 2. С. 465-466 . URL: https://doi.org/10.32837/11300.33259
Keywords: digitalization; criminal proceedings; procedural safeguards; protection of business economic interests; e-court; cybersecurity; martial law; цифровізація; кримінальне провадження; процесуальні гарантії; захист економічних інтересів бізнесу; електронний суд; кіберзахист; воєнний стан